The gypsies - Fraser, Angus M.; Mazal Holocaust Collection (Oxford, UK ; Cambridge, USA : Blackwell, 1995)
Traces the history of the Gypsies from their origins in India through the twentieth-century, examines their distinctive culture, and discusses how they managed to survive despite enslavement, harassment, and prejudice.
1. Origins -- The linguistic evidence -- Physical anthropology -- Ethnic parallels -- Lexicostatistics -- 2. Early Migrations -- Persia -- Armenia -- Social cohesion -- 3. Into the Byzantine Empire and the Balkans -- Byzantium and Greece -- Serbia, Bulgaria, Wallachia, Moldavia -- 4. The Great Trick -- Imperial safe-conducts -- New letters of protection -- Taking stock -- 5. The Turn of the Tide -- Germany, Austria, Switzerland -- France -- Spain and Portugal -- The Low Countries -- Italy -- Hungary and Transylvania -- Bohemia, Poland-Lithuania and the Ukraine -- Scotland and England -- Scandinavia -- Images and stereotypes -- European patterns -- 6. Pressure of the Gyves -- Expulsion, assimilation, extirpation -- Transportation -- Within the Ottoman Empire -- Survival of the species -- Scant glimmerings of light -- 7. Forces for Change -- New perceptions -- Musical ascendancies -- Landscapes and townscapes -- Out of bondage -- Renewed migrations -- Conservation and mutation -- 8. The Approach to Avernus -- 'Combating the Gypsy nuisance' -- The forgotten holocaust -- 9. Modern Times -- Frontier crossings -- Questions of policy -- Populations and groupings -- Turns of speech -- Tradition of change -- Pilgrims and Pentecostals -- Opre Roma!
Includes bibliographical references (pages 321-341) and index.
Keywords: Romanies -- Europe -- History; Europe -- Ethnic relations; Ethnic relations; Romanies; Gypsies